1773PShort-term outcomes of cancer patients with pulmonary embolism according to the setting (hospital-acquired vs. outpatient) at diagnosis. (1st October 2019) - Muñoz Guglielmetti, D; Pesántez, D; Posch, F; Ay, C; Aramberri, M; Beato Zambrano, M D C; Diaz-Pedroche, C; Font, C
Abstract: Background: Pulmonary embolism (PE) is a common condition in patients with cancer, having a wide spectrum of clinical presentation (from acute life-threatening to truly asymptomatic incidental events). The aim of this study was to assess the prognostic relevance of the variable 'setting' (hospital-acquired vs. outpatient) at PE diagnosis. Methods: Multicenter observational ongoing registry of consecutive patients with cancer-associated PE (2005-2018) including incidental and acute symptomatic events. The main outcome measured was the rate of overall and PE-specific 30-day mortality. Secondary outcomes were: rates of 30-day major bleeding (MB) and venous thromboembolism (VTE) recurrence. Results: We included a total of 617 patients (61.6% male; median age 65 + 11.4 years; range 19-91 years) including N = 522 (85%) outpatients and N = 95 (15%) inpatients at PE diagnosis. The most frequent primary tumors were: lung 32%, colorectal 14%, urologic 13%, upper GI 12%, breast 9%, gynecologic 6% and other 9%). Most of the patients (79%) had metastatic cancer and nearly half (47%) were receiving chemotherapy.The PE was incidentally found in 54% of the cases. Overall 30-day mortality occurred in 95 patients (15% of the cohort), being greater in inpatients compared to outpatients (30% vs. 13%; p < 0.0001). Only 13 patients presented PE-related mortality (3% of the cohort), with no significant differences according to the setting at PE diagnosis (3.2% in inpatients vs. 1.7% in outpatients; p = 0.352). Similarly, there were no differences in 30-day MB (7.4% in inpatients vs. 4.4% in outpatients; p = 0.217) or VTE recurrence (4.2% in inpatients vs. 3.3% in outpatients; p = 0.637) according to the setting at PE diagnosis. Conclusions: Hospital-acquired PE in cancer patients was associated with a greater overall 30-day mortality compared to outpatients at PE diagnosis. This finding may be relevant for the development of PE risk-assessment models in this setting. Legal entity responsible for the study: Hospital Clínic de Barcelona. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.